2012
DOI: 10.1108/00907321211254698
|View full text |Cite
|
Sign up to set email alerts
|

A LibGuides presence in a Blackboard environment

Abstract: Purpose-This paper aims to describe current approaches to and assess the value of placing course-level research guides generated through LibGuides software into Blackboard learning management system (LMS) shells. It also aims to describe the specific technique of such placement in Blackboard Vista and Blackboard Learn shells. Design/methodology/approach-A link to a library assignment made with LibGuides was embedded as a button in the left-side navigation bar of the Blackboard shell for an undergraduate commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Fisher and Heaney (2011, 41) suggest that "inside" library support is critical for students who are at risk of dropping out. Embedded librarians are in a better position to assist students to appreciate the standards that are expected of them; mentor them into the discourse of research and information literacy; model effective processes of academic thinking and information evaluation in the context of their discipline (Fisher and Heaney 2011); and, provide point-of-need services to students (Bowen 2012). As insiders, librarians are seen by students as part of the teaching team.…”
Section: Support Through Embedded Practicementioning
confidence: 99%
“…Fisher and Heaney (2011, 41) suggest that "inside" library support is critical for students who are at risk of dropping out. Embedded librarians are in a better position to assist students to appreciate the standards that are expected of them; mentor them into the discourse of research and information literacy; model effective processes of academic thinking and information evaluation in the context of their discipline (Fisher and Heaney 2011); and, provide point-of-need services to students (Bowen 2012). As insiders, librarians are seen by students as part of the teaching team.…”
Section: Support Through Embedded Practicementioning
confidence: 99%
“…(Head & Eisenberg, 2010) Bowen's study also confirmed that students who used a library guide accessed from within the LMS found the guide useful for finding resources. (Bowen, 2012) This demonstrates that embedding library guides in the LMS is an effective way to assist students with information tasks that research shows are most challenging to them.…”
Section: Discussionmentioning
confidence: 96%
“…In 2012 studies, for instance, two separate research teams surveyed users and/or non-users of library guides. (Bowen, 2012;Leeder, Lonn, & Hollar, 2012) In both studies, however, the guides themselves were only delivered to sub-sets of the university. The study reported in this article is unique in that it explores usage of guides delivered to all courses within a university's LMS.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mahaffy (2012) reported the results of two focus group conversations on how students used guides and what they would like to see on them. Bowen (2012) presents the first published instructions documenting how to embed a LibGuide into the BlackBoard learning management system (LMS), paired with a student evaluation of accessing their guide via BlackBoard. Murphy and Black (2013) follow up with their own study of student response to library guides in their LMS.…”
Section: Libguidesmentioning
confidence: 99%